Sibyls, scriptures and scrolls John Collins at seventy - Collins, John J. 1946-; Baden, Joel S. 1977-; Najman, Hindy 1967-; Tigchelaar, Eibert J. C. 1959- (Leiden Boston Brill, 2017)
Preliminary Material Volume 1 -- Introduction /Joel Baden , Hindy Najman and Eibert Tigchelaar -- Between Athens and Jerusalem, on the Wings of a Dove? /Susan Ackerman -- The Social Location of the Scribe in the Second Temple Period /Samuel L. Adams -- Heraclitus’s Homeric Problems and Midrash Genesis Rabbah: Comparisons and Contrasts /Philip Alexander -- The Identification of the “Wicked Priest” Reconsidered: The Case for Hyrcanus ii /Kenneth Atkinson -- What’s in a Name? Naming the Unnameable in Philo and John /Harold W. Attridge -- Redactor or Rabbenu? Revisiting an Old Question of Identity /Joel S. Baden -- Old Testament Ethics: Story or Style? /John Barton -- Future Food and Future Feasting: Tracing the Idea of the Meal in the World to Come in Qumran Literature /Claudia D. Bergmann -- Casting Lots and Distributing Territories: The Hellenistic Background of the Book of Jubilees and the Genesis Apocryphon /Katell Berthelot -- Authority and Propaganda—The Case of the Potter’s Oracle /Stefan Beyerle -- How Jesus Became Uncreated /Gabriele Boccaccini -- Thrēskeia in 4 Maccabees /Daniel Boyarin -- The Visualisation of the Sacred at Qumran /George J. Brooke -- The Wisdom of the Nations and the Law of Israel: Genealogies of Ethnic Difference in Ben Sira and the Mekhilta /Joshua Ezra Burns -- Zechariah, Zerubbabel, and Zemah: Ideological Development in Early Postexilic Judah /Laura Carlson -- The Divine Assembly in Genesis 1–11 /Richard J. Clifford -- The Enochs of Genesis 4 and 5 and the Emergence of the Apocalyptic Enoch Tradition /John Day -- Genre Analysis and Early Christian Martyrdom Narratives: A Proposal /Michal Beth Dinkler -- The Disappearing God in Ezekiel the Tragedian /Robert Doran -- Scent of a Woman: The Influence of Lady Wisdom on 2 Maccabees 7:20–29 /Antonios Finitsis -- Preserving the Cult of yhwh in Judean Garrisons: Continuity from Pharaonic to Ptolemaic Times /Anne Fitzpatrick-McKinley -- “If a Case is Too Baffling for You to Decide . . .” (Deuteronomy 17:8–13): Between Constraining and Expanding Judicial Autonomy in the Temple Scroll and Early Rabbinic Scriptural Interpretation /Steven D. Fraade -- Of Doves, Fish, and Goddesses: Reflections on the Literary, Religious, and Historical Background of the Book of Jonah /Eckart Frahm -- Fire and Water? Apocalyptic Imagination and Hellenistic Worldview in 2 Peter /Jörg Frey -- Where’s Enoch? The Mythic Geography of the Qumran Book of Giants /Matthew Goff -- Josephus and Jewish Ethnicity /Erich S. Gruen -- Cutting the Cord with the Familiar: What Makes 4Q265 Miscellaneous Rules Tick? /Charlotte Hempel -- The Dream of a Perfect Text: Textual Criticism and Biblical Inerrancy in Early Modern Europe /Ronald Hendel -- “I Am the Judge”: Judgment in the Apocalypse of Abraham /Matthias Henze -- Mother Zion in Baruch 4:5–5:9 and 2 Baruch 1–12: A Study of Different Models of Intertextuality /Karina Martin Hogan -- Scribal Innovation and the Book of Tobit: A Long Overdue Discussion /Naomi S. S. Jacobs -- What is “Serekh ha-Yahad (S)”? Thinking About Ancient Manuscripts as Information Processing /Jutta Jokiranta.
This volume, a tribute to John J. Collins by his friends, colleagues, and students, includes essays on the wide range of interests that have occupied John Collins’s distinguished career. Topics range from the ancient Near East and the Hebrew Bible to the Dead Sea Scrolls and Second Temple Judaism and beyond into early Christianity and rabbinic Judaism. The contributions deal with issues of text and interpretation, history and historiography, philology and archaeology, and more. The breadth of the volume is matched only by the breadth of John Collins’s own work
Keywords: Bible -- Criticism, interpretation, etc; Dead Sea Scrolls; Rabbinical literature -- History and criticism; Apocalyptic Literature -- History and criticism